Bearing the burden — Implications of tax reporting institutions on evasion and incidence - Kotakorpi, Kaisa (Elsevier, 2025)
We investigate effects of tax reporting institutions on evasion and incidence using an experimental double auction market. We find that 28% of the sellers are truthful when only sellers report, but that 88% and 64% of them are truthful under costless and costly third-party reporting by buyers, respectively. Reporting behavior therefore responds to the intensity of deterrence. However, we find that prices do not fully reflect the lower taxes of the evaders. Thus, when sellers can unilaterally evade taxes, tax incidence deviates from the prediction of the standard model, and there is deadweight loss even if tax revenue is low. Pricing, incidence, and reporting patterns in all treatments are consistent with a model with heterogeneous lying costs, or a combination of lying costs and image concerns that give rise to a motivation to appear honest.